The Dinamics Of Islamic Colleges In South Sumatera: Problems And Challenges - Eko Nopriyansa (STAI Bumi Silampari, 2021)
This article is an outcome of the research and thorough study toward central issues in developing religious studies on Islamic Colleges in South Sumatra. In the management system and institutional development of Islamic education, the human resources’ role plays a vital role in achieving the national Islamic Colleges program in Indonesia. This writing describes a more comprehensive research outcome on various dynamics and academic problems in several Islamic Colleges in the South Sumatra region. Some essential issues such as problems in education and the scientific publication, scientific journal system and resources management, availability on education Infrastructure and facilities, qualified and supporting Islamic books availability, and overall challenges faced by several Islamic Colleges in South Sumatra become the strict attention in this research. Data or information derived in this research through several field studies, both in interview and observation, until collecting various sources through transcript or written document possessed by some Islamic Colleges in the South Sumatra region. This research has delivered recommendations or important input in developing and managing Indonesian Islamic Colleges, Indonesia in general, particularly in South Sumatra.